Wild sheep chase - Haruki Murakami (London Vintage Books, 2003)
A Wild Sheep Chase has the conventional hull of a thriller - a quest, a mystery, an extraordinary woman, and plenty of elegant duress - but its fantastic superstructure transforms it into something quite different...a science fiction fantasy, a romance, a metaphysical tease, or a dramatisation of philosophical ideas' Independent.
Keywords: English Fiction